Língua, patrimônio nosso - Cervo, Larissa Montagner (2012)
This work addresses the meaning of language as patrimony from a specific place, the Portuguese Language Museum (São Paulo, 2006), elected for constituting a safeguard and a celebration space of the patrimony, besides showing the language as a symbolic object. The concept of patrimony involves a series of symbols that are socially and juridically determined from the value and symbolic strength they have for the collective memory of a group. It is a material means of witnessing the past lived by the discursive paraphrase of memories with content of historical temporality, and this paraphrase is inscribed in the universe of the logically established discourses. In this perspective, language is also valorized in the space of the subjects practices and of what is manifested as representative of this relationship. So it must be a part of or remain in the narratives of history. Mainly, due to the authorized voice of the museum as a place in the material culture, an authorized place to interpret and a place for fixing senses, the constitution of the language as a museum object, and, therefore, a patrimony, problematizes both the possibility of the language to be a file and the legitimization of a discourse through which facts and versions that serve as references in our history are organized and presented (ORLANDI, 2000). Our theoretical and methodological approach is the Discourse Analysis postulated by Michel Pêcheux in France and developed by Eni Orlandi and other researchers in Brazil. From this perspective, we start with the comprehension of language as a material basis and as a condition to realize different discursive processes (PÊCHEUX, 2009 [1988]), and we try to work it as a symbolic object that slides through distinct senses, i.e., both in its imaginary character and as a possibility of creating facts in the world. The remission to the concepts of imaginary and fluid language (ORLANDI, 2003 [1999]) is the possibility to reflect the theory on the political practice of discursive appreciation and stabilization of the language as a symbolic object in the constitution of the file at the Portuguese Language Museum. The way to be followed involves the deconstruction of the file and of the file memory of that museum toward the constitution of language as patrimony, with a value of historical memory and in its political sense, relating to the universality previewed in the concept of patrimony and in the museum slogan: language is what unites us .